Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If a,b,c, are in AP prove that: 1.(a-c)^2=4(a-b)(b-c)

If a,b,c, are in AP prove that: 1.(a-c)^2=4(a-b)(b-c)

Grade:11

2 Answers

Arun
25763 Points
4 years ago
Take RHS
4(a-b)(b-c)
Expand it
4[ab -ac -b^2 +bc]
Use 2b = a +c.       Because a,b,c are in A.P.
4[(a+c)(a+c)/2 -ac - (a+c)^2]
= a^2 + c^2 - 2ac
= (a -c)^2
= LHS
Hence proved
Shailendra Kumar Sharma
188 Points
4 years ago
To prove(a-c)^2=4(a-b)(b-c)Or{ (a-c)^2}/}(a-b)(b-c)} =4 ...... 1Given a,b,c are in A.P. assume the common difference be d than b-a= c-b= d And c-a= 2dPut values in LHS of 14d^2/d^2=4 = RHS

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free